1990
DOI: 10.1192/bjp.156.3.363
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Schizophrenia in Croatia

Abstract: Hospital-based annual incidence rates for schizophrenia in Croatia over 1965-84 did not change significantly. Rates ranged from 0.21 to 0.22 per 1,000 population (0.26-0.29 per 1,000 population aged over 15). Factors that could influence these rates were analysed, but it appeared that the rates were a true reflection of the incidence rate of schizophrenia in the Croatian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Out of 100 core studies, 39 studies report rates only for persons [33,40,45,47,48,55-57,59,61,73,75,79,86,87,116,91,93-96,99,103,104,107-109,112-114,118,120-122,124-127,183,192], 16 report rates only for males and females [41,63,68,74,82,102,110,111,116,117,119,123,187-190], and 45 studies report rates for persons, males, and females [13,31,46,49-54,58,60,65-67,69-72,76-78,80,81,83-85,88-90,92,97,98,100,101,105,106,115,148,180-182,184-186,191]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of 100 core studies, 39 studies report rates only for persons [33,40,45,47,48,55-57,59,61,73,75,79,86,87,116,91,93-96,99,103,104,107-109,112-114,118,120-122,124-127,183,192], 16 report rates only for males and females [41,63,68,74,82,102,110,111,116,117,119,123,187-190], and 45 studies report rates for persons, males, and females [13,31,46,49-54,58,60,65-67,69-72,76-78,80,81,83-85,88-90,92,97,98,100,101,105,106,115,148,180-182,184-186,191]. …”
Section: Resultsmentioning
confidence: 99%
“…Thirty seven discrete-core studies report rates only for persons [31,33,45-49,55-57,59,61,65,71,73,75,76,78,79,85,86,88,91,93-96,99,103,104,107,112,114,121,124-126,180,190], 13 report rates only for males and females [41,50,52,53,67,74,82,102,111,116,123,188,189], and 18 studies report rates for persons, males, and females [13,51,54,58,60,69,70,72,77,80,83,84,92,97,98,100,101,106]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a limited number of studies have explored changes in the incidence of schizophrenia over a period of time, suggesting both a decline 13,14 and an increase, 15 and yet other studies have shown stability. 16,17 Variations in the methodological approaches may justify the inconsistencies reported in the epidemiology of schizophrenia. Thus, to make a valid estimation and analysis of the incidence, the studies have to incorporate in their designs a series of requisites: first, a well-defined administrative and sociodemographic catchment area should be established; second, all first episodes should be recruited from the general population or at least from contacts with any available health service; third, the assessment and diagnostic process should assure adequate levels of validity and reliability; and finally, the design should guarantee the control of possible confounding factors and the incorporation of clear operational criteria to define the factors associated with the risk for schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Oldehinkel and Giel found no decrease in the in ci dence of schizo phre nia when a broader def ini tion of the dis or der was used (7). Folnegovi and oth ers con cluded that the change from ICD-7 to ICD-9 over the course of their study did not in flu ence the re corded in ci dence rates (8). Nicole and oth ers com pared nonvalidated ICD-9 diag no ses of schizo phre nia with di ag no ses val i dated by case notes and found a lower rate when they ap plied their own stricter cri te ria (16).…”
Section: Discussionmentioning
confidence: 98%